2008
DOI: 10.1016/j.febslet.2008.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Human fortilin is a molecular target of dihydroartemisinin

Abstract: Dehydroartemisinin (DHA) is an effective anti-malaria agent. Fortilin is an anti-apoptotic molecule overexpressed in many human cancers. Here, we show that DHA binds human fortilin, increases the ubiquitination of fortilin, shortens fortilinÕs half-life in a proteasome-dependent fashion, and reduces cellular levels of fortilin in varieties of cells. DHA induced DNA fragmentation in U2OS cells in a fortilin-dependent manner. The fortilin-knocked-down cells were less susceptible-and fortilinoverexpressing cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 16 publications
(25 reference statements)
2
36
0
Order By: Relevance
“…Three kinds of drugs (DHA, sertraline and thioridazine) were reported as the direct anti-cancer drug targets for TCTP. Fujita et al demonstrated that DHA could bind to human TCTP and decrease its cellular level through promoting ubiquitination and proteasomedependent degradation (Fujita et al, 2008;Lucibello et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Three kinds of drugs (DHA, sertraline and thioridazine) were reported as the direct anti-cancer drug targets for TCTP. Fujita et al demonstrated that DHA could bind to human TCTP and decrease its cellular level through promoting ubiquitination and proteasomedependent degradation (Fujita et al, 2008;Lucibello et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Artemisinin not only displays antimalarial activity but was also found to be a potent anticancer agent in cellular assay (review in Efferth 2005), and screening for potential targets in this context has confirmed that TCTP is indeed a target for this drug (Efferth 2005(Efferth , 2006. The interaction of artemisinin with TCTP was then studied in cancer cells, and it was found that drug treatment results in degradation of TCTP (fortilin) via the ubiquitin-proteasome pathway (Fujita et al 2008). More recent publications described proof-of-principle investigations for the use of artemisinin as an anticancer drug in cellular models of lung cancer , of Neurofibromatosis type 1 (NF1)-associated tumours (Kobayashi et al 2014) and of breast cancer (Lucibello et al 2015).…”
Section: Tctp As An Anticancer Targetmentioning
confidence: 99%
“…Recently, certain artemisinin derivatives, especially dihydroartemisinin (DHA), were shown to have anticancer eVects in a wide variety of cancer models in vitro and in vivo, including breast cancer (Singh and Lai 2001), cervical cancer (Chen et al 2003), ovarian cancer (Chen et al 2003;Jiao et al 2007), glioma (Huang et al 2007), lung cancer (Mu et al 2008), leukemia (Singh and Lai 2005), Wbrosarcoma (Singh and Lai 2004), osteosarcoma (Fujita et al 2008), oral cancer (Nam et al 2007) and hepatoma (Hou et al 2008). The mechanisms of action for their antitumor activities are not fully understood, but may include induction of G 0 /G 1 cell cycle arrest (Hou et al 2008;EVerth et al 2003), increased apoptosis (Singh and Lai 2001;Jiao et al 2007;Huang et al 2007;Mu et al 2008;Singh and Lai 2004;Fujita et al 2008;Nam et al 2007;Hou et al 2008), inhibition of angiogenesis and lymphangiogenesis (Chen et al 2003;Wu et al 2006;Wang et al 2007), and increased sensitization to radiation and anticancer drugs (Singh and Lai 2001;Kim et al 2006).…”
Section: Introductionmentioning
confidence: 99%